COLUMN GENRE IN AZERBAIJAN LITERATURE HISTORY OF DEVELOPMENT - Simuzar Aliyeva (International Journal of Innovative Technologies in Social Science, 2023)
The feuilleton genre has a wide and very interesting history of development in Azerbaijani literature. What happened in the social and political life of the people, the weight of social processes, the difficulty of life, the problems caused by the war and the occupation made it a necessity in the writing style of the environment. The development of the periodical press and the hard realities of life necessitated the feuilleton as a form as the most concise and brilliant artistic example of social consciousness. It has created the necessary conditions for the timely investigation of specific areas of hard life truths. H. Zardabi, H. Vazirov, J. Mammadguluzade, N. Narimanov, U. Hajibeyli, H. I. Gasimov, A. Gamkusar, etc. it is impossible to study and research the rich creative activity of writers in isolation from the columnist’s creativity. In general, the period of fiction, as well as column, comes to the press literally with the publication of "Akinchi" newspaper. "Akinchi" newspaper fought against formalism on a large scale in the world of literature and art in general. A typical example of this is clearly shown by the attitude towards religious - lamentation literature and other fields. Lamentism, which has no importance for the progress of the people, gives way to different approaches and special sensitivity is shown to its harmful aspects. All these and other problems are expressed in detail in the column.